In Vitro Hydrodynamic Performance Evaluation of Valve Repair System - Liang CAI; Yibin LI; Shiwen LYU (Zhongguo yiliao qixie zazhi)
ObjectiveTo meet the treatment requirements for mitral regurgitation disease, this study designed a novel valve repair system and evaluated its hydrodynamic performance. MethodsA mitral regurgitation model was created. The valve repair system was loaded onto the regurgitation model, and pulsatile flow tests and steady backflow leakage tests were conducted. ResultsThe pulsatile flow test results indicated that the percentage of reflux after product implantation was lower than that before implantation under different concentric outputs and reverse pressures. The average cross-valve pressure difference after implantation was less than 5 mmHg. The steady backflow leakage test results showed that as the reverse pressure increased, the leakage amount of the valve repair system after implantation also increased. ConclusionThe developed valve repair system exhibits excellent hydrodynamic performance, suggesting the feasibility of its application in the treatment of clinical mitral regurgitation.